Research on characteristic flow areas of large thermal power generating units based on EBSILON simulation - LI Jun; LI Wei; MAO Jingyu; LI Long; CHEN Liming; YANG Dianbing; YU Xiaogang (Zhejiang dianli, 2025)
To monitor the flow performance of peak-shaving units online， simulation models for coal-fired generator units with three different parameter levels （subcritical， supercritical， and ultra-supercritical） were developed using EBSILON. The variations in characteristic flow areas of each stage of the units under different operating conditions were studied， and the deviation range and influencing factors of these flow areas were analyzed. Based on performance test data， a unit performance diagnostic process was proposed and implemented in a power plant. The calculation results show that the characteristic flow areas of the middle stages of the units remain largely unchanged， and the heating steam extraction does not affect the characteristic flow areas of adjacent stages. Therefore， the characteristic flow area parameters obtained through EBSILON simulation and calculation can serve as a crucial indicator for evaluating unit performance. By establishing a performance data archive for the units， further performance analysis， operational monitoring， and fault diagnosis can be facilitated.